The imperatives of trans-national approach to reforming educational assessment for African regional development (2012)
This paper examines the imperatives of trans-national approach to reforming educational assessment for African regional development. It state that educationa is a major pivot for human development and regional development. The need for trans-national approach is informed by the fact that human development indicies in African countries are among the least globally, thus indicating a state of underdevelopment, as other forms of development are human driven. The essence of the paper is to describe how collaborating in research, test development, monitoring and test security can engeder improvement of the African examing system for effective and efficient education delivery and African development. The study is a descriptive one, drawing its sample from Anglophone West Africa. A check list as used to collect the views of some stakeholders on enhancing educational assessment reforms through partnership among African examining bodies for improved African examining system to enhanceing effective education delivery, cooperative test development and administration, monitoring of the public examining system, promoting test security of the African public examining. The data were analyzed utilizing percentages and graphs. It ws found that an African synergistic approach to public examining would be more beneficial than individualistic approach. Stakeholders also observed that African collaborative research in public confidence in the system as well as help minimize examination fraud and could also be cost-effective. An examining system competence based cooperative mechanism (akin to the comparative advantage model) was suggested for adoption for collaboration.